Fabrication of Aluminum Alloy with Open-Channel and Columnar Structures through a Ceramic Fiber Template Method - Hideo Nakajima (Metals, 2023)
Aluminum alloys with open-channel and columnar structures were fabricated by casting the melt of aluminum alloys using a ceramic fiber template method. Stainless steel plates or wires coated with ceramic fibers impregnated by polyvinyl alcohol were used as cores. The cores were embedded in a melt of an aluminum alloy. After solidification, the ceramic fibers were macerated and became sodden by immersing the aluminum alloy ingots in water so that the plates or wires were easily removed by extraction forces as large as 5N, in other words, by pulling out them manually. Thus, an open-channel aluminum alloy was fabricated by a simple method. On the other hand, ceramic fiber blocks composed of ceramic fibers impregnated by polyvinyl alcohol were perforated by microdrills. Melts of aluminum alloy were cast in the holes by a vacuum suction method. The ceramic fibers were removed by immersing the ingots in water. Thus, a columnar-structured aluminum alloy was produced. Previous methods for the fabrication of open-channel metals necessitates a process to extract the metallic wires embedded in the solidified metals. However, the ceramic fiber template method does not require such an extraction process and thus is a very simple technique for the fabrication of open-channel metals, such as porous metals with rectangular holes and circular holes and columnar structures metals.